Sistem Informasi Akademik Berbasis Web pada SMK Pelayaran Sinar Bahari Palembang - Kornelia* Kornelia*; Emi Yuliati; Dedy Hermanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2014)
The purpose of the author of this thesis is to provide an alternative to the process of learning and teaching in SMK Sinar Bahari Palembang. The problems at SMK Sinar Bahari Palembang is the academic and non-academic information can only be obtained in the school environment. in this issue the authors use iterative methods in a web-based Academic Information System. In the design phase the authors use tools such as context diagrams, decomposition diagrams, DAD, ERD, STD Charts and display interfaces in accordance with the proposed. Web-based Academic Information System Could made easy way for parents and student to access that school gives.